CHEMICAL CASTRATION FROM CRIMINAL LAW AND HUMAN RIGHTS - Dina Silvia Puteri; Denita Cahyanti Wahono; Rr. Jannatul Firdaus; Steven Sukamdani (Universitas Lampung, 2020)
Chemical castration is an additional penalty for child sexual abuse stipulated under Protection of Children Law, which states that anyone who intentionally commits sexual violence against children in any way and with certain criminal elements is subject to additional penalties in the form of chemical castration. As an additional penalty, chemical castration is excessive and deprives the right to reproduction. The criminal application also explicitly overrides state protection of human rights based on international conventions such as the ICCPR and UNCAT 1948 which has been ratified by Indonesia Human Rights Law. The implementation of chemical castration in Indonesia may able to reduce the number of habitual crimes or recidivists on sexual offender still raise the pros and cons. On the other hand, the effectiveness of this method in preventing these crimes is still debatable. The Indonesian Doctors Association (IDI) rejects the assignment of the execution because the additional penalty execution by the doctor is in contrary to the Indonesian Medical Ethics Code. This study aims to find solutions to conflict of law that occur in the application of chemical castration in the perspective of criminal law and human rights.